“OMO HADA” Arsitektur Tradisional Nias Selatan Diambang Kepunahan - Syuaib Intan, Muhammad Fadhlan; Nasruddin, Nasruddin (KALPATARU, 2018)
AbstractThe South Nias cultural heritage presented through the artifacts, in the form of traditional architectural buildings, as well as various megalithic stone buildings with all their forms, is an ancestral cultural work that not only contains aesthetic values, uniqueness and art, but also local wisdom as a source of knowledge which is very valuable to be studied and studied. This important and very valuable heritage must be preserved and preserved. But the attitudes and views of the people towards their cultural heritage are changing, as if they no longer have sacred values, even the value of local wisdom begins to fade over time. The existence of South Nias traditional houses is relatively more sustainable compared to other traditional houses. To maintain its existence, changes are needed to accommodate the current residential needs of the community. On the other hand, these changes have the potential to eliminate the character or authenticity of traditional Nias Selatan architecture. This study aims to find out about traditional technologies and architectural changes that occur and their impact on the existence of traditional South Nias houses. From the various problems of the South Nias cultural heritage that are being faced, this study tries to highlight aspects of traditional architecture and local wisdom, including the accompanying megalithic elements. The subjects that will be studied use an ethno-archaeological approach with emphasis on the observation method through direct observation of objects of material culture and social aspects at the research site. In this way it makes it easier for us to observe directly and in detail the architectural forms and components, both exterior and interior as well as the decorative types in the past cultural context of South Nias.Keywords: Traditional Architecture, Megalithic, Cultural HeritageAbstrak Warisan budaya Nias Selatan yang dipresentasikan lewat  peninggalan artefak, berupa  bangunan berarsitektur tradisional, maupun beragam bangunan batu megalit dengan segala rupa bentuknya, merupakan karya budaya leluhur  yang tidak hanya mengandung nilai estetika, keunikan dan seni semata, tetapi juga merupakan kearifan lokal sebagai sumber ilmu pengetahuan yang sangat berharga untuk dikaji dan dipelajari.  Warisan yang penting dan sangat berharga  ini wajib dipelihara dan dilestarikan. Namun sikap dan pandangan masyarakatnya  terhadap warisan budayanya, sedang berubah, seakan tidak lagi memiliki nilai-nilai sakral, bahkan  nilai kearifan lokal pun mulai luntur seiring perjalanan waktu. Keberadaan rumah tradisional Nias Selatan relatif lebih bertahan eksistensinya dibandingkan rumah tradisional lainnya. Untuk mempertahankan eksistensinya, diperlukan perubahan untuk mengakomodasi kebutuhan hunian masyarakat saat ini. Di sisi lain, perubahan tersebut berpotensi menghilangkan karakter atau keaslian  arsitektur tradisional Nias Selatan. Kajian ini bertujuan untuk mengetahui teknologi tradisional dan perubahan arsitektur yang terjadi dan dampaknya terhadap eksistensi dari rumah tradisional Nias Selatan. Dari berbagai masalah warisan budaya Nias Selatan yang sedang dihadapi itu,  maka penelitian ini mencoba menyoroti aspek  arsitektur tradisional maupun kearifan lokalnya, termasuk unsur megalitik yang menyertainya. Subyek yang akan  dikaji ini memakai pendekatan etnoarkeologi dengan  penekanan  pada metode  observasi melalui pengamatan langsung terhadap obyek-obyek budaya material dan aspek sosial di lokasi penelitian. Dengan cara ini memudahkan kita mengamati secara langsung dan detil bentuk-bentuk arsitektur dan komponennya, baik eksterior dan interior maupun ragam hias dalam konteks budaya masa lalu Nias Selatan.Kata Kunci: Arsitektur Tradisional, Megalitik, Warisan Budaya